In Vitro Bacterial Competition of Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli against Coagulase-Negative Staphylococci from Bovine Mastitis Milk - Anyaphat Srithanasuwan; Montira Intanon; Wasana Chaisri; Witaya Suriyasathaporn (MDPI AG, 2023)
Intramammary infection (IMI) from the environment and infected quarters can cause co-infection. The objective of this study was to determine the ability of coagulase-negative staphylococci (CNS) to survive in the same environment as Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli as major pathogens. In total, 15 and 242 CNS strains were used in Experiment I and Experiment II, respectively. Both experiments were separated into three conditions: culture with CNS 24 h before (PRIOR), after (AFTER), and at the same time (EQUAL). The lack of a clear zone, regardless of size, was determined to be the key to the survival of both. The CNS species' percentages of survival against major pathogens were tested using Fisher's exact test. Differences in the percentages of survival were evident among the CNS species in all conditions. For the PRIOR condition, all CNS mostly survived when living with major strains; however, S. chromogenes could degrade S. agalactiae. Although most CNS strains were degraded in the AFTER and EQUAL conditions, some strains of S. hominis and S. simulans could resist S. aureus and S. agalactiae. In conclusion, some specific strains of CNS are able to survive in an environment with major pathogens. Research into the survival strains may indicate that the concept of novel bacteria with bacteriolytic capabilities might be possible as a novel mastitis treatment.